Impaired Interoceptive Accuracy in Semantic Variant Primary Progressive Aphasia - Marshall, Charles R.; Hardy, Chris J. D.; Russell, Lucy L.; Clark, Camilla N.; Dick, Katrina M.; Brotherhood, Emilie V.; Bond, Rebecca L.; Mummery, Catherine J.; Schott, Jonathan M.; Rohrer, Jonathan D.; Kilner, James M.; Warren, Jason D. (Frontiers in Neurology, 2017)
Background: Interoception (the perception of internal bodily sensations) is strongly linked to emotional experience and sensitivity to the emotions of others in healthy subjects. Interoceptive impairment may contribute to the profound socio-emotional symptoms that characterize frontotemporal dementia syndromes, but remains poorly defined. Methods: Patients representing all major frontotemporal dementia syndromes and healthy age-matched controls performed a heartbeat counting task as a measure of interoceptive accuracy. Additionally, patients had volumetric MRI for voxel based morphometric analysis, and their caregivers completed a questionnaire assessing patients’ daily-life sensitivity to the emotions of others. Results: Interoceptive accuracy was impaired in patients with semantic variant primary progressive aphasia relative to healthy age-matched individuals, but not in behavioural variant frontotemporal dementia and nonfluent variant primary progressive aphasia. Impaired interoceptive accuracy correlated with reduced daily-life emotional sensitivity across the patient cohort, and with atrophy of right insula, cingulate and amygdala on voxel-based morphometry in the impaired semantic variant group, delineating a network previously shown to support interoceptive processing in the healthy brain. Conclusion: Interoception is a promising novel paradigm for defining mechanisms of reduced emotional reactivity, empathy and self-awareness in neurodegenerative syndromes, and may yield biomarkers for these complex symptoms.